Plant regeneration from inflorescence cultures of Gynandropsis pentaphylla DC. - Nagarathnamma,M. Sudarshana,M.S. and Niranjan,M.H (Journal of Applied Pharmaceutical Science, 2013)
An efficient protocol for shoot regeneration from immature inflorescence of Gynandropsis pentaphylla DC (Capparidaceae) is described. Healthy inflorescences were cultured on MS medium supplemented with BAP, Kn, zeatin, TDZ (0.5 - 5.0 mg/l) alone and in combination with IAA, NAA, IBA (0.5 - 2.0 mg/l). BAP (3.0 mg/l) with IBA (1.0 mg/l) as well as Kn (1.0 mg/l) with TDZ (0.1 mg/l) were found to be effective in inducing callus and in production of shoots and roots. The present investigation also describes the histological studies depicting various stages that occurred during the development of embryoids and shoot buds. The species is so potential that the flower buds on the medium induces callus from each part of the flower bud. All the in vitro raised shoots were transferred to MS rooting liquid medium supplemented with 0.5 - 1.0 mg/l IAA, NAA and IBA. Well rooted plantlets were transferred to polycups containing soil : vermiculite (1:1) for hardening. Finally the hardened plantlets were transferred to field conditions for maximum survivability. The flower is mixoploid and hence the regenerated roots were squashed in acetoorcein to know the ploidy level of the regenerated shoots. All the plants regenerated were shown to be diploid.
Keywords: Gynandropsis pentaphylla DC.,inflorescence culture,plant regeneration.